2003
DOI: 10.2165/00003088-200342090-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions with Rifampicin

Abstract: The antituberculosis drug rifampicin (rifampin) induces a number of drug-metabolising enzymes, having the greatest effects on the expression of cytochrome P450 (CYP) 3A4 in the liver and in the small intestine. In addition, rifampicin induces some drug transporter proteins, such as intestinal and hepatic P-glycoprotein. Full induction of drug-metabolising enzymes is reached in about 1 week after starting rifampicin treatment and the induction dissipates in roughly 2 weeks after discontinuing rifampicin. Rifamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
516
1
19

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 639 publications
(562 citation statements)
references
References 209 publications
14
516
1
19
Order By: Relevance
“…Verapamil, which increased the intestinal absorption of cyclosporine and tacrolimus in this study, has previously been reported to be a substrate of P-gp when used in low doses and to strongly inhibit P-gp when used high doses [8]. Furthermore, it has been suggested that rifampicin activates P-gp in vivo and in vitro [11,12]. Although there are some other studies about the effects of P-glycoprotein modulation on the bioavailability of several drugs [16][17][18], to best of the authors' knowledge, this is the first study to investigate the effects of P-gp-inhibiting and -activating drugs on the intestinal absorption of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Verapamil, which increased the intestinal absorption of cyclosporine and tacrolimus in this study, has previously been reported to be a substrate of P-gp when used in low doses and to strongly inhibit P-gp when used high doses [8]. Furthermore, it has been suggested that rifampicin activates P-gp in vivo and in vitro [11,12]. Although there are some other studies about the effects of P-glycoprotein modulation on the bioavailability of several drugs [16][17][18], to best of the authors' knowledge, this is the first study to investigate the effects of P-gp-inhibiting and -activating drugs on the intestinal absorption of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, P-gp can easily be activated by some agents, such as rifampicin [11,12]. P-glycoprotein plays an important role in the intestinal absorption of immunosupressive agents, including cyclosporine and tacrolimus [13][14][15].…”
mentioning
confidence: 99%
“…In comparison, when 6 mg midazolam was given orally with 200 mg ketoconazole, midazolam Cmax and AUC(0,•) were increased 4-fold and 13.6-fold compared with midazolam alone [13]. When oral midazolam was given with rifampicin at steady-state, the midazolam AUC was decreased 96-98% [11].…”
Section: Discussionmentioning
confidence: 96%
“…On day 9, tolvaptan 240 mg and rifampicin 600 mg were simultaneously administered to subjects in the fasted state. Rifampicin administration has been reported to decrease the concentrations of weak CYP3A4 substrates such as midazolam by 96-98% [11].…”
Section: Rifampicin (Inducer) Trialmentioning
confidence: 99%
“…90,91 It was recently reported that concomitant administration of rifampin at a dose of 600 mg/day for 10 days in healthy volunteers reduced digoxin plasma concentrations substantially after an oral single-dose (1 mg) administration compared with the plasma-time profile without rifampin treatment. 92 The effect was less pronounced after intravenous administration of digoxin.…”
Section: Drug Interactions After Treatment With Rifampinmentioning
confidence: 99%